Relación entre el control simultáneo y gestión financiera en la Municipalidad Provincial de Ramón Castilla en la región Loreto 2025 - Marin Sanchez, Barbara Stephany (2025)
This research aimed to analyze the relationship between concurrent control and financial management in the Provincial Municipality of Ramón Castilla, located in the Loreto region of Peru, during the year 2025. A quantitative approach was employed, using a non-experimental design, applied type, and correlational level. The sample consisted of 185 municipal workers, who responded to a structured Likert-scale questionnaire assessing perceptions on key variables such as supervision frequency, corrective actions, staff training in internal control, and efficiency in financial resource management. The results revealed a positive and statistically significant correlation between concurrent control and financial management (Spearman’s rho = 0.684; p = 0.001), confirming that the effective implementation of real-time control mechanisms contributes to improving budgetary execution, meeting financial objectives, and enhancing institutional transparency. Additionally, specific hypotheses were validated linking components of control to concrete dimensions of financial management. The findings underscore the strategic role of concurrent control in public administration and suggest both recommendations and structural proposals to strengthen its institutional application at the municipal level.